0D and 2D nanomaterials based on Graphene Quantum Dots and MXenes: synthesis, characterization and application in sensors and supercapacitors. - FACURE, M. H. M. (2023)
ABSTRACT 0D AND 2D NANOMATERIALS BASED ON GRAPHENE QUANTUM DOTS AND MXENES APPLIED IN SENSORS AND SUPERCAPACITORS. Graphene Quantum Dots (GQDs) are small fragments of one or a few layers of graphene with lateral dimensions inferior to 100 nm. GQDs present some characteristics similar to those of graphene, such as a high surface area/volume ratio and chemical stability. In addition, GQDs present a bandgap between their valence and electronic conduction bands. This bandgap gives rise to one of the most investigated properties of GQDs: their photoluminescence, which enables their application as luminescent sensors. In this sense, in the first work, hydrothermal syntheses of GQDs from graphene oxide (GO) were studied aiming at obtaining a material with greater photoluminescence intensity for application in luminescent sensors. The synthesis temperature, pH of the GO solution, and GO concentration were evaluated to optimize the quantum yield of GQDs. An optimized value of 8.9% was obtained. The influence of each parameter on the composition and properties of the GQDs was carried out from the physical-chemical characterization of the materials. The synthesized materials were used in the detection of Fe3+ ions in aqueous solutions by luminescence quenching, obtaining a detection limit of 0.136 M. Like GQDs, the discovery of a new class of materials known as MXenes was inspired by the discovery of graphene. MXenes are 2D materials, in which transition metal layers are interleaved with carbon and/or nitrogen layers. Such materials have demonstrated high energy storage capacity, being widely exploited in devices such as supercapacitors and batteries. However, the restacking of the MXene layers and the narrow potential window usually obtained limit the performance of these materials in such applications. In another work, nanodiamonds (NDs) were used to prevent the restacking of the MXene layers during its use as a supercapacitor electrode. The pillaring effect obtained with the NDs allowed a greater diffusion of protons between the layers of the MXene Ti3C2Tx, resulting in a capacitance of 235 F/g (561 F/cm3 ) when used in 3 M AlCl3 electrolyte. Furthermore, a wide potential window of 1.2 V could be used due to the reduced water activity in the electrolyte.